2019
DOI: 10.1016/j.bjpt.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of 95% confidence intervals in the reporting of between-group differences in randomized controlled trials: analysis of a representative sample of 200 physical therapy trials

Abstract: Objectives: To assess the prevalence of the use of 95% confidence intervals in the reporting of between-group differences in randomized controlled trials of physical therapy interventions and to determine if the prevalence is changing over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
19
0
3
Order By: Relevance
“…A paper published within this issue of the Brazilian Journal of Physical Therapy (BJPT) raised a very interesting, important and relevant matter for evidence-based practice: the use of the 95% confidence interval (CI) for reporting the uncertainty around between-group comparisons in randomized controlled trials investigating the effects of physical therapy interventions. 1 Briefly, the study found that: (1) only less than one-third of physical therapy trials report CIs; (2) trials with lower risk of bias (i.e., higher quality) are more likely to report CIs; and (3) there has been a consistent increase in reporting CIs over time. 1 The increasing trend on reporting CIs is good news for physical therapy evidencebased practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A paper published within this issue of the Brazilian Journal of Physical Therapy (BJPT) raised a very interesting, important and relevant matter for evidence-based practice: the use of the 95% confidence interval (CI) for reporting the uncertainty around between-group comparisons in randomized controlled trials investigating the effects of physical therapy interventions. 1 Briefly, the study found that: (1) only less than one-third of physical therapy trials report CIs; (2) trials with lower risk of bias (i.e., higher quality) are more likely to report CIs; and (3) there has been a consistent increase in reporting CIs over time. 1 The increasing trend on reporting CIs is good news for physical therapy evidencebased practice.…”
Section: Introductionmentioning
confidence: 99%
“…1 Briefly, the study found that: (1) only less than one-third of physical therapy trials report CIs; (2) trials with lower risk of bias (i.e., higher quality) are more likely to report CIs; and (3) there has been a consistent increase in reporting CIs over time. 1 The increasing trend on reporting CIs is good news for physical therapy evidencebased practice. Nevertheless, clinicians should understand CIs so they can appropriately interpret results of trials in order to better implement such evidence in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the confidence interval of the average value is − / , + / , where = / is the corresponding standard score. In general, the confidence probability in the literature [42,45,46] is 90% or 95%, and / is 1.645 or 1.96, respectively.…”
Section: Confidence Intervalmentioning
confidence: 99%
“…Nearly 100 factors were summarized to reveal the commonly used factors. In accordance with the relevant studies [29,41,42] and the study area, we select eight influencing factors: elevation, topography, slope, lithology, distance to a structure line, distance to a river, average annual rainfall, and distances to roads. Table 1 lists all the DEM data for the study area and their sources.…”
Section: Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation